Main challenges in Nursing teaching: a systematic review of literature (Research, Society and Development, 2020)
Nursing teaching has been facing several difficulties that have generated negative impacts for both the teacher and the student. This study aims to communicate the results of a consolidated analysis of data obtained in the 1st and 2nd stages of a systematic literature review, in which the main challenges of nursing teacher education in the last 15 years were investigated. This is a qualitative approach research with systematization of data called 'State of Art', contemplating the foundations of Discursive Textual Analysis for data analysis. The survey of papers with Qualis stratification A1, A2, B1 and B2 was performed in the Nursing Evaluation Area. In total 12 journals and 23 papers were found covering the theme Nursing Teaching. The main challenges observed were the lack of pedagogical preparation of the nurse teacher during and after graduation, their difficulty in re-elaborating their teaching methodologies and relying on the traditional curriculum rather than the integrated curriculum. It is suggested that the Higher Education Institutions that offer undergraduate Nursing courses, in addition to providing training for nurses in care, provide pedagogical training through disciplines focused on teaching.